LR B-Splines implementation in the Altair RadiossTM solver for explicit dynamics IsoGeometric Analysis. (May 2019) - Occelli, M.; Elguedj, T.; Bouabdallah, S.; Morançay, L.
Highlights: Isogeometric analysis is introduced in the explicit dynamics commercial software Altair Radioss TM . A 3D solid element using B-splines and NURBS is introduced. An existing penalty based contact interface is extended to deal with spline-based and Lagrange-based finite elements in the same model. LR B-splines is introduced to allow for local refinement. A method to generate trivariate LRB-splines locally refined meshes with guaranteed linear independence and absence of overloading is introduced. Several industrial benchmark demonstrated the efficiency of the approach. Abstract: IsoGeometric Analysis has shown to be a very promising tool for an integrated design and analysis process. A challenging task is still to move IGA from a proof of concept to a convenient design tool for industry and this work contributes to this endeavor. This paper deals with the implementation of the IGA concept into Altair Radioss finite element solver in order to address crash and stamping simulation applications. To this end, the necessary ingredients to a smooth integration of IGA in a traditional finite element code have been identified and adapted to the existing code architecture. A solid B-Spline element has been developed in Altair Radioss and then, an existing contact interface has been extended in order to work seamlessly with both NURBS and Lagrange finite elements. As local refinement is needed for solution approximation, an analysis is made in terms of analysis suitability and implementation aspects for several Spline technologies. The Locally Refined B-Spline (LRBS) technology is implemented and is validated on industrial benchmarks, for validation cases conventionally used for industrial codes like stamping and drop test.